IMPLEMENTASI PEMBELAJARAN E-LEARNING MADRASAH DALAM MOTIVASI BELAJAR SISWA MATA PELAJARAN FIQIH KELAS VIIIMTS TARBIYAH ISLAMIAH HINAI KIRI - Hazijah Hazijah; Nurmisdaramayani Nurmisdaramayani; Usmaidar Usmaidar (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2023)
The background is that during Covid 19 learning was done online or distance learning (PJJ) made students less motivated in learning, therefore, Madrasah E-Learning based learning was applied. The objectives of this research were: To find out how the implementation of Madrasah E-Learning learning in the learning motivation of students in the Fiqh subject class VIII MTs Tarbiyah Islamiah Hinai Kiri. This research is an experimental type of research with a quantitative approach. However, there is no denying the existence of a qualitative approach to knowing and analyzing data on teacher abilities in implementing Madrasah E-Learning-based learning. The results showed that the application of Madrasah E-Learning in learning Fiqh could increase the learning motivation of class VIII MTs Tarbiyah Islamiyah Hinai Kiri, from the beginning of the pre-action to the end of cycle II. The results of the initial questionnaire on student learning motivation reached a percentage of 58%, and at the end of cycle I, the results of the questionnaire on student learning motivation reached a percentage of 68% and at the end of cycle II the results of the questionnaire reached 75%.